2022
DOI: 10.3390/vaccines10091498
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Immune Responses to COVID-19 Vaccines in Bangladeshi Population

Abstract: Background: The adaptive immune response is a crucial component of the protective immunity against SARS-CoV-2, generated after infection or vaccination. Methods: We studied antibody titers, neutralizing antibodies and cellular immune responses to four different COVID-19 vaccines, namely Pfizer-BioNTech, Moderna Spikevax, AstraZeneca and Sinopharm vaccines in the Bangladeshi population (n = 1780). Results: mRNA vaccines Moderna (14,655 ± 11.3) and Pfizer (13,772 ± 11.5) elicited significantly higher anti-Spike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Nevertheless, differences in immune response regarding different type of vaccines could already be observed, which might have in influence on the course of breakthrough infections. 16 COVID-19 vaccination involves numerous immune responses such as activation of lymphocytes and producing of neutralising antibodies. However, other pathways such as kinetics involved in cytokines and their receptors, and stimulation of non-T cell responses remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, differences in immune response regarding different type of vaccines could already be observed, which might have in influence on the course of breakthrough infections. 16 COVID-19 vaccination involves numerous immune responses such as activation of lymphocytes and producing of neutralising antibodies. However, other pathways such as kinetics involved in cytokines and their receptors, and stimulation of non-T cell responses remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with findings from several immune response studies on COVID-19 vaccines in human populations ( 27 31 ). In a recently conducted community-based study in Bangladesh, mRNA vaccine recipients showed higher antibody response than adenovector and killed whole-virus vaccine recipients ( 24 ). The S protein of SARS-CoV-2 is used as the immunogen in the Pfizer/Comirnaty, Moderna/Spikevax, and AstraZeneca/Covishield vaccines to generate anti-S antibodies that block the S protein’s binding to host cell ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…A strong correlation between past SARS-CoV-2 infection and higher anti-S antibodies was also seen. Recently, in five major divisions of Bangladesh, persons with previous SARS-CoV-2 infection were shown to have higher post-vaccine immunological responses compared to non-infected individuals ( 24 ). In another study in the Bangladeshi population, after immunization, those with a record of SARS-CoV-2 infection had six times higher antibody titers than those without a history of infection ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations